N-doped carbon coated Bi x Sb 1-x Nanoparticle electrode material and preparation method and application thereof

By coating the BixSb1-x nanoparticle electrode material with N-doped carbon, the problems of low conductivity and easy structure failure in lithium-ion batteries are solved, and the electrochemical performance of high cycling stability and discharge capacity are achieved.

CN115588740BActive Publication Date: 2025-04-08WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110760762.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-05
Publication Date
2025-04-08
Estimated Expiration
2041-07-05

AI Technical Summary

Technical Problem

As the negative electrode material of lithium-ion batteries, BixSb1-x has low conductivity and its structure is easily damaged during charging and discharging, resulting in poor circulation performance, limiting its application.

Method used

N-doped carbon is used to coat the BixSb1-x nanoparticle electrode material, and the carbon shell is coated by the solvent-free method to improve the mechanical stability and electron/ion conduction ability of the electrode material.

Benefits of technology

It effectively alleviates the structural damage caused by volume expansion during charge and discharge of BixSb1-x nanoparticles, improves cyclic stability and discharge capacity, and shows excellent rate performance and capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003146944590000011
    Figure HDA0003146944590000011
  • Figure HDA0003146944590000012
    Figure HDA0003146944590000012
  • Figure HDA0003146944590000021
    Figure HDA0003146944590000021
Patent Text Reader

Abstract

The present invention relates to N-doped carbon coated Bi x Sb 1‑x Nanoparticle electrode material and its preparation method and application. The N-doped carbon coated Bi x Sb 1‑x The nanoparticle electrode material is an amorphous N-doped carbon coated core-shell structure. x Sb 1‑x The average particle size of the nanoparticles is within the range of 20-30nm, and the size of the nanoparticles is within the range of 10-50nm; the size of the core-shell structure is 100-400nm. x Sb 1‑x Nanoparticle electrode materials can make Bi x Sb 1‑x The structural damage caused by volume expansion during the charge and discharge process is effectively alleviated, while also improving the ion / electron transmission capacity of the electrode material, reducing its diffusion path, and greatly improving Bi x Sb 1‑x The cyclic stability of nanoparticle electrode materials. Moreover, the present invention prepares N-doped carbon-coated Bi by a solvent-free method. x Sb 1‑x Nanoparticle negative electrode materials, when used as negative electrode active materials for lithium-ion batteries, exhibit the characteristics of high discharge capacity and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanomaterials and electrochemical technology, and specifically relates to N-doped carbon coated Bi x Sb 1-x Nanoparticle electrode material, preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have played a key role in the rapid development of portable electronics and electric vehicles. For a long time, graphite has been used as a traditional negative electrode material for lithium-ion batteries due to its relatively flat potential plateau, high conductivity and stable layered structure. However, its low lithium insertion potential easily leads to the formation of lithium dendrites, which causes safety problems. x Sb 1-x As a negative electrode material for lithium-ion batteries, Bi has a higher theoretical capacity than the currently used graphite and has considerable potential as a negative electrode material for lithium-ion batteries. x Sb 1-x As a traditional thermoelectric semiconductor material, its electrical conductivity is not high, and the inevitable volume expansion during the charging and discharging process causes its structure to be destroyed and its cycle performance to be poor, which limits its application.

[0003] At present, coating method has attracted more and more attention in the field of electrochemistry and energy due to its series of excellent properties. Common coating can be divided into carbon-inorganic core-shell structure nanomaterials and polymer / inorganic core-shell structure nanomaterials. Currently, BiSb is rarely used as the negative electrode of lithium-ion batteries, so there is basically no research on the coating modification of BiSb alloy in the field of lithium battery negative electrode. Summary of the invention

[0004] The problem to be solved by the present invention is to provide a N-doped carbon-coated Bi x Sb 1-x Nanoparticle electrode materials have high electronic / ionic conductivity and structural integrity during lithium storage, showing excellent cycling stability.

[0005] Another object of the present invention is to provide an N-doped carbon-coated Bi x Sb 1-x Preparation method and application of nanoparticle electrode materials.

[0006] The technical solution adopted by the present invention to solve the above problems is:

[0007] N-doped carbon coated Bi x Sb 1-x Nanoparticle electrode material, characterized in that it is N-doped carbon coated Bi x Sb1-x The core-shell structure formed by nanoparticles has a size of 100-400nm. x Sb 1-x The average particle size of the nanoparticles is in the range of 20-30nm, and the size of the nanoparticles is in the range of 10-50nm. Wherein, 0<X<1, and the X value is calculated according to the stoichiometric ratio; Bi x Sb 1-x The mass percentage of the nanoparticles in the core-shell structure is in the range of 55%-65%.

[0008] The above N-doped carbon coated Bi x Sb 1-x The method for preparing nanoparticle electrode material comprises the following steps:

[0009] 1) Dispersing BiCl3 and SbCl3 together in deionized water to obtain a milky white suspension;

[0010] 2) Slowly add disodium ethylenediaminetetraacetate solution, polyvinylpyrrolidone solution and NaBH4 solution to the milky white suspension obtained in step 1), and perform ultrasonic reaction at a certain temperature for a period of time to obtain a black solution; the black solution is subjected to solid-liquid separation, washed and dried, and the obtained solid product is Bi x Sb 1-x Nanoparticles; 3) Bi x Sb 1-x Nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 were blended and ground under a protective atmosphere to obtain a black viscous substance; the black viscous substance was transferred to an autoclave for solidification, and the solidified substance was annealed in flowing argon to obtain N-doped carbon-coated Bi x Sb 1-x Nanoparticle electrode materials.

[0011] According to the above scheme, the total concentration of BiCl3 and SbCl3 in the milky white suspension described in step 1) is 0.03-0.1 mol / L; the molar ratio of BiCl3 and SbCl3 is X:(1-X), 0<X<1.

[0012] According to the above scheme, the molar ratio of (BiCl3+SbCl3), NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:(5-15):(1-2):(1-2).

[0013] According to the above scheme, the concentration of NaBH4 solution is 5-7 mol / L, the concentration of disodium ethylenediaminetetraacetate solution is 2-3 mol / L, and the concentration of polyvinylpyrrolidone solution is 2-3 mol / L; NaBH4 solution, disodium ethylenediaminetetraacetate solution and polyvinylpyrrolidone solution all use deionized water as solvent.

[0014] According to the above scheme, in step 2), the ultrasonic time is 0.5-3h, and the ultrasonic temperature is 30-60°C.

[0015] According to the above scheme, the Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine and poloxamer Pluronic F127 is (2-10): (2-4): 1: (8-10).

[0016] According to the above scheme, the curing temperature in step 3) is 100-200°C, and the curing time is 12-36h; the annealing temperature is 600-800°C, and the annealing time is 3-8h; and the argon flow rate is 40mL / min.

[0017] The N-doped carbon-coated Bi x Sb 1-x Application of nanoparticle electrode materials as negative electrode active materials for lithium-ion batteries.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] First, the present invention uses a solvent-free method to coat N-doped carbon on Bi x Sb 1-x On the surface of nanoparticles, the carbon shell has high mechanical stability and can act as a buffer layer to make Bi x Sb 1-x The structural damage caused by the volume expansion of nanoparticles during the charge and discharge process is effectively alleviated, while also improving the ion / electron transmission capacity of the electrode material, reducing its diffusion path, and greatly improving Bi x Sb 1-x Cycling stability of nanoparticle electrode materials;

[0020] Moreover, the N-doped carbon-coated Bi x Sb 1-x Nanoparticle negative electrode materials, when used as negative electrode active materials for lithium-ion batteries, exhibit the characteristics of high discharge capacity and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The N-doped carbon-coated Bi of Example 1 of the present invention 0.5 Sb 0.5 SEM image of nanoparticle electrode material;

[0022] Figure 2 The N-doped carbon-coated Bi of Example 1 of the present invention 0.5 Sb 0.5TEM image of nanoparticle electrode material;

[0023] Figure 3 Bi before and after N-doped carbon coating of Example 1 of the present invention 0.5 Sb 0.5 XRD pattern of nanoparticle electrode material;

[0024] Figure 4 Bi before and after N-doped carbon coating of Example 1 of the present invention 0.5 Sb 0.5 Raman images of nanoparticle electrode materials;

[0025] Figure 5 The N-doped carbon-coated Bi of Example 1 of the present invention 0.5 Sb 0.5 Battery rate diagram of nanoparticle electrode materials;

[0026] Figure 6 The N-doped carbon-coated Bi of Example 1 of the present invention 0.5 Sb 0.5 Battery cycling performance diagram of nanoparticle electrode materials. DETAILED DESCRIPTION

[0027] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.

[0028] In the following examples, the molecular formula of disodium ethylenediaminetetraacetate is C 10 H 14 N2O8Na2·2H2O.

[0029] Example 1

[0030] N-doped carbon coated Bi x Sb 1-x A method for preparing a nanoparticle electrode material comprises the following steps:

[0031] 1) 3.025 g NaBH4 was dissolved in 15 ml deionized water, 3.723 g disodium ethylenediaminetetraacetate and 1.11 g polyvinylpyrrolidone were dissolved in 5 ml deionized water respectively, and the latter two were ultrasonicated for 1 hour to obtain transparent solutions, which were 5.33 mol / L NaBH4 solution, 2 mol / L disodium ethylenediaminetetraacetate solution, and 2 mol / L polyvinylpyrrolidone solution (the concentration of the polymer was calculated based on the molar concentration of the monomer C6H9NO);

[0032] 2) 1.5618 g BiCl3 and 1.1041 g SbCl3 were dissolved in 100 ml deionized water and ultrasonicated for 30 min to obtain a milky suspension, and then 5 ml of disodium ethylenediaminetetraacetic acid solution, 5 ml of polyvinylpyrrolidone solution, and 15 ml of NaBH4 solution were slowly added in sequence through a syringe, and ultrasonicated for 2 h at 40°C to obtain a black solution; wherein the molar ratio of BiCl3 to SbCl3 is 1:1; the molar ratio of BiCl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetic acid and polyvinylpyrrolidone (the molar ratio of the polymer is calculated based on the monomer) is 1:8:1:1;

[0033] 3) The black solution was first washed three times with alcohol by centrifugation, and then washed three times with deionized water by centrifugation at a speed of 10000 rpm for 3 min, and then freeze-dried for 12 h to obtain Bi 0.5 Sb 0.5 Nanoparticles;

[0034] 4) In an Ar-filled glove box, 0.347 g Bi 0.5 Sb 0.5 The mixture of nanoparticles, 0.33 g m-phenylenediamine, 0.1 g hexamethylenetetramine, and 0.83 g poloxamer Pluronic F127 was ground for 30 min to obtain a black viscous substance; wherein, Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 is 3.47:3.3:1:8.3;

[0035] 5) The black viscous material was transferred to an autoclave and cured at 160°C for 24 h. The cured material was annealed at 600°C for 4 h in flowing argon to obtain N-doped carbon-coated Bi 0.5 Sb 0.5 Nanoparticle electrode materials.

[0036] like Figure 1 As shown, the SEM image shows that a certain amount of Bi is encapsulated inside the N-doped carbon sphere. 0.5 Sb 0.5 Nanoparticles;

[0037] like Figure 2 As shown, TEM images show: N-doped carbon coated Bi 0.5 Sb 0.5 Nanoparticles become core-shell structures. 0.5 Sb 0.5 The nanoparticles are distributed inside the carbon spheres, the average particle size of the nanoparticles is in the range of 20-30nm, and the size of the nanoparticles is in the range of 10-50nm; the size of the core-shell structure is 100-400nm.

[0038] In this embodiment, N-doped carbon coated Bi 0.5 Sb 0.5 Take nanoparticle materials as an example, whose structure is determined by X-ray diffractometer. Figure 3 As shown, the X-ray diffraction pattern (XRD) shows that the Bi obtained in step 3) 0.5 Sb 0.5 Nanoparticle material and Bi coated with N-doped carbon obtained in step 5) 0.5 Sb 0.5 The nanoparticle material is basically consistent with the card number BiSb (PDF#85-1331).

[0039] like Figure 4 As shown, Raman spectroscopy shows that N-doped carbon coated Bi 0.5 Sb 0.5 The nanoparticle material is N-doped carbon.

[0040] The N-doped carbon-coated Bi 0.5 Sb 0.5 The application of nanoparticle materials as negative electrode active materials for lithium-ion batteries is as follows: The preparation process of the positive electrode sheet is to coat Bi with N-doped carbon 0.5 Sb 0.5 Nanoparticles are used as active materials; acetylene black is used as a conductive agent, polyvinylidene fluoride is used as a binder, and the mass ratio of active materials, acetylene black, and polyvinylidene fluoride is 70:20:10; after they are fully mixed in proportion, a small amount of isopropanol is added, and they are evenly ground and pressed into electrode sheets with a thickness of about 0.5 mm on a roller mill; the pressed positive electrode sheets are placed in an oven at 80°C and dried for 24 hours for use. 1M LIPF6 is dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC) as an electrolyte, a lithium sheet is used as a negative electrode, Celgard2500 is used as a separator, and CR2032 stainless steel is used as a battery shell to assemble a button-type lithium-ion battery. The preparation method of the lithium-ion battery and the remaining steps are the same as the usual preparation method.

[0041] like Figure 5 As shown in the figure, at current densities of 100mAh / g, 200mAh / g, 500mAh / g, 1000mAh / g, 1500mAh / g, 2000mAh / g, and 3000mAh / g, N-doped carbon coated Bi 0.5 Sb 0.5 The first discharge specific capacity of the nanoparticle materials can reach 606, 502, 425, 400, 353, 297, and 266 mAh / g, respectively; moreover, N-doped carbon-coated Bi 0.5 Sb 0.5The nanoparticle material has excellent rate performance. After charging and discharging at different current densities of 100mAh / g-3000mAh / g, the capacity of the material at a current density of 100mAh / g can be restored to 536mAh / g, indicating that the material has very good rate performance.

[0042] like Figure 6 As shown in Figure , at a current density of 1000 mAh / g, N-doped carbon coated Bi 0.5 Sb 0.5 The specific capacity of the nanoparticle material in the second cycle is 583.5 mAh / g. After 2000 cycles of charge and discharge, the capacity is still 489.4 mAh / g, and the capacity retention rate is 84%. The above performance shows that N-doped carbon coated Bi 0.5 Sb 0.5 Nanoparticle materials have very excellent electrochemical properties and are a potential negative electrode material for lithium-ion batteries.

[0043] Example 2

[0044] N-doped carbon coated Bi x Sb 1-x A method for preparing a nanoparticle electrode material comprises the following steps:

[0045] 1) 3.025 g NaBH4 was dissolved in 15 ml deionized water, 3.723 g disodium ethylenediaminetetraacetate and 1.11 g polyvinylpyrrolidone were dissolved in 5 ml deionized water respectively, and the latter two were ultrasonicated for 1 hour to obtain transparent solutions, namely, 5.33 mol / L NaBH4 solution, 2 mol / L disodium ethylenediaminetetraacetate solution, and 2 mol / L polyvinylpyrrolidone solution;

[0046] 2) 1.5618g BiCl3 and 1.1041g SbCl3 were dissolved in 100ml deionized water and ultrasonicated for 30min to obtain a milky suspension, and then 5ml disodium ethylenediaminetetraacetate, 5ml polyvinylpyrrolidone solution and 15ml NaBH4 solution were slowly added in sequence through a syringe, and ultrasonicated for 2h at 40°C to obtain a black solution; wherein the molar ratio of BiCl3 to SbCl3 is 1:1; the molar ratio of BiCl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:8:1:1;

[0047] 3) The black solution was first centrifuged and washed three times with alcohol, then centrifuged and washed three times with deionized water, the centrifugal speed was 10000 rpm, the time was 3 min, and then freeze-dried for 12 h to obtain Bi 0.5 Sb 0.5 Nanoparticles;

[0048] 4) In an Ar-filled glove box, 0.2 g Bi 0.5 Sb 0.5 The mixture of nanoparticles, 0.33 g m-phenylenediamine, 0.1 g hexamethylenetetramine, and 0.83 g poloxamer Pluronic F127 was ground for 30 min to obtain a black viscous substance; wherein, Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 was 2:3.3:1:8.3;

[0049] 5) The black viscous material was transferred to an autoclave and cured at 160°C for 24 h. The cured material was annealed at 600°C for 4 h in flowing argon to obtain N-doped carbon-coated Bi 0.5 Sb 0.5 Nanoparticle electrode materials.

[0050] At a current density of 1000 mAh / g, the N-doped carbon-coated Bi 0.5 Sb 0.5 The second discharge specific capacity of the nanoparticle material can reach 383 mAh / g, and the discharge specific capacity after 2000 cycles is 295 mAh / g, with a capacity retention rate of 77%.

[0051] Example 3

[0052] N-doped carbon coated Bi x Sb 1-x A method for preparing a nanoparticle electrode material comprises the following steps:

[0053] 1) 3.025g NaBH4 was dissolved in 15ml deionized water, 3.723g disodium ethylenediaminetetraacetate and 1.11g polyvinylpyrrolidone were dissolved in 5ml deionized water respectively, and the latter two were ultrasonicated for 1h to obtain transparent solutions; the concentration of NaBH4 solution was 5.33mol / L, the concentration of disodium ethylenediaminetetraacetate solution was 2mol / L, and the concentration of polyvinylpyrrolidone solution was 2mol / L respectively;

[0054] 2) 1.5618g BiCl3 and 1.1041g SbCl3 were dissolved in 100ml deionized water and ultrasonicated for 30min to obtain a milky suspension, and then 5ml disodium ethylenediaminetetraacetate, 5ml polyvinylpyrrolidone solution and 15ml NaBH4 solution were slowly added in sequence through a syringe, and ultrasonicated for 2h at 40°C to obtain a black solution; wherein the molar ratio of BiCl3 to SbCl3 is 1:1; the molar ratio of BiCl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:8:1:1;

[0055] 3) The black solution was first washed three times with alcohol by centrifugation, and then washed three times with deionized water by centrifugation at a speed of 10000 rpm for 3 min. Finally, Bi was obtained after freeze drying for 12 h. 0.5 Sb 0.5 Nanoparticles;

[0056] 4) In an Ar-filled glove box, 1 g Bi 0.5 Sb 0.5 The mixture of nanoparticles, 0.33 g m-phenylenediamine, 0.1 g hexamethylenetetramine, and 0.83 g poloxamer Pluronic F127 was ground for 30 min to obtain a black viscous substance; wherein, Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 was 10:3.3:1:8.3;

[0057] 5) The black viscous material was transferred to an autoclave and cured at 160°C for 24 h. The cured material was annealed at 600°C for 4 h in flowing argon gas to finally obtain N-doped carbon-coated Bi 0.5 Sb 0.5 Nanoparticle electrode materials.

[0058] The N-doped carbon-coated Bi 0.5 Sb 0.5 As an example, at a current density of 1000 mAh / g, N-doped carbon-coated Bi 0.5 Sb 0.5 The second discharge specific capacity of the nanoparticle material can reach 615 mAh / g, and the discharge specific capacity after 2000 cycles is 306 mAh / g, with a capacity retention rate of 49.8%.

[0059] Example 4

[0060] N-doped carbon coated Bi x Sb 1-x A method for preparing a nanoparticle electrode material comprises the following steps:

[0061] 1) 3.025 g NaBH4 was dissolved in 15 ml deionized water, 7.446 g disodium ethylenediaminetetraacetate and 2.22 g polyvinylpyrrolidone were dissolved in 10 ml deionized water respectively, and the latter two were ultrasonicated for 1 hour to obtain transparent solutions, namely, 5.33 mol / L NaBH4 solution, 2 mol / L disodium ethylenediaminetetraacetate solution, and 2 mol / L polyvinylpyrrolidone solution;

[0062] 2) 1.5618g BiCl3 and 1.1041g SbCl3 were dissolved in 100ml deionized water and ultrasonicated for 30min to obtain a milky suspension, and then 10ml disodium ethylenediaminetetraacetate, 5ml polyvinylpyrrolidone solution, and 15ml NaBH4 were slowly added in sequence through a syringe, and ultrasonicated for 2h at 40°C to obtain a black solution; wherein the molar ratio of BiCl3 to SbCl3 is 1:1; the molar ratio of BiCl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:8:2:1;

[0063] 3) The black solution was first centrifuged and washed three times with alcohol, and then centrifuged and washed three times with deionized water, with a centrifugal speed of 10000 rpm for 3 min. After freeze drying for 12 h, Bi 0.5 Sb 0.5 Nanoparticles;

[0064] 4) In an Ar-filled glove box, 0.347 g Bi 0.5 Sb 0.5 The mixture of nanoparticles, 0.33 g m-phenylenediamine, 0.1 g hexamethylenetetramine, and 0.83 g poloxamer Pluronic F127 was ground for 30 min to obtain a black viscous substance; wherein, Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 is 3.47:3.3:1:8.3;

[0065] 5) The black viscous material was transferred to an autoclave and cured at 160°C for 24 h. The cured material was annealed at 600°C for 4 h in flowing argon to obtain N-doped carbon-coated Bi 0.5 Sb 0.5 Nanoparticle electrode materials.

[0066] At a current density of 1000 mAh / g, the N-doped carbon-coated Bi 0.5 Sb 0.5 The second discharge specific capacity of the nanoparticle material can reach 420 mAh / g, and the discharge specific capacity after 2000 cycles is 326 mAh / g, with a capacity retention rate of 77.6%.

[0067] Example 5

[0068] N-doped carbon coated Bi x Sb 1-x A method for preparing a nanoparticle electrode material comprises the following steps:

[0069] 1) 3.025 g NaBH4 was dissolved in 15 ml deionized water, 3.723 g disodium ethylenediaminetetraacetate and 1.11 g polyvinylpyrrolidone were dissolved in 5 ml deionized water respectively, and the latter two were ultrasonicated for 1 hour to obtain transparent solutions, namely, 5.33 mol / L NaBH4 solution, 2 mol / L disodium ethylenediaminetetraacetate solution, and 2 mol / L polyvinylpyrrolidone solution;

[0070] 2) Dissolve 2.2075g BiCl3 and 0.6855g SbCl3 in 100ml deionized water and ultrasonicate for 30min to obtain a milky suspension, then slowly add 5ml disodium ethylenediaminetetraacetate, 5ml polyvinylpyrrolidone solution and 15ml NaBH4 in sequence through a syringe, and ultrasonicate for 2h at 40°C to obtain a black solution; wherein the molar ratio of BiCl3 to SbCl3 is 7:3; the molar ratio of BiCl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:8:1:1;

[0071] 3) The black solution was first centrifuged and washed three times with alcohol, and then centrifuged and washed three times with deionized water, with a centrifugal speed of 10000 rpm for 3 min. After freeze drying for 12 h, Bi 0.7 Sb 0.3 Nanoparticles;

[0072] 4) In an Ar-filled glove box, 0.384 g Bi 0.7 Sb 0.3 The mixture of nanoparticles, 0.33 g m-phenylenediamine, 0.1 g hexamethylenetetramine, and 0.83 g poloxamer Pluronic F127 was ground for 30 min to obtain a black viscous substance; wherein, Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 is 3.84:3.3:1:8.3;

[0073] 5) The black viscous material was transferred to an autoclave and cured at 160°C for 24 h. The cured material was annealed at 600°C for 4 h in flowing argon to obtain N-doped carbon-coated Bi 0.7 Sb 0.3 Nanoparticle electrode materials.

[0074] At a current density of 1000 mAh / g, the N-doped carbon-coated Bi 0.7 Sb 0.3 The second discharge specific capacity of the nanoparticle material can reach 400 mAh / g. After 2000 cycles, the discharge specific capacity is 293 mAh / g, and the capacity retention rate is 73.3%.

[0075] Example 6

[0076] 1) 3.025 g NaBH4 was dissolved in 15 ml deionized water, 3.723 g disodium ethylenediaminetetraacetate and 1.11 g polyvinylpyrrolidone were dissolved in 5 ml deionized water respectively, and the latter two were ultrasonicated for 1 hour to obtain transparent solutions, namely, 5.33 mol / L NaBH4 solution, 2 mol / L disodium ethylenediaminetetraacetate solution, and 2 mol / L polyvinylpyrrolidone solution;

[0077] 2) 0.9461g BiCl3 and 1.5995g SbCl3 were dissolved in 100ml deionized water and ultrasonicated for 30min to obtain a milky suspension, and then 5ml disodium ethylenediaminetetraacetate, 5ml polyvinylpyrrolidone solution and 15ml NaBH4 were slowly added in sequence through a syringe, and ultrasonicated for 2h at 40°C to obtain a black solution; wherein the molar ratio of BiCl3 to SbCl3 is 3:7; the molar ratio of BiCl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:8:1:1;

[0078] 3) The black solution was first centrifuged and washed three times with alcohol, and then centrifuged and washed three times with deionized water, with a centrifugal speed of 10000 rpm for 3 min. After freeze drying for 12 h, Bi 0.3 Sb 0.7 Nanoparticles;

[0079] 4) In an Ar-filled glove box, 0.311 g Bi 0.3 Sb 0.7 The mixture of nanoparticles, 0.33 g m-phenylenediamine, 0.1 g hexamethylenetetramine, and 0.83 g poloxamer Pluronic F127 was ground for 30 min to obtain a black viscous substance; wherein, Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine, and poloxamer Pluronic F127 is 3.11:3.3:1:8.3;

[0080] 5) The black viscous material was transferred to an autoclave and cured at 160°C for 24 h. The cured material was annealed at 600°C for 4 h in flowing argon to obtain N-doped carbon-coated Bi 0.3 Sb 0.7 Nanoparticle electrode materials.

[0081] At a current density of 1000 mAh / g, the N-doped carbon-coated Bi 0.3 Sb 0.7The second discharge specific capacity of the nanoparticle material can reach 430 mAh / g. After 2000 cycles, the discharge specific capacity is 266 mAh / g, and the capacity retention rate is 61.9%.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. N-doped carbon coated Bi x Sb 1-x Nanoparticle electrode material, characterized in that It is N-doped carbon coated Bi x Sb 1-x The core-shell structure formed by nanoparticles has a size of 100-400nm. x Sb 1-x The average particle size of nanoparticles is 20-30nm; The N-doped carbon coated Bi x Sb 1-x The method for preparing nanoparticle electrode material comprises the following steps: 1) Dispersing BiCl3 and SbCl3 together in water to obtain a milky white suspension; 2) slowly adding disodium ethylenediaminetetraacetate solution, polyvinylpyrrolidone solution and NaBH4 solution to the milky white suspension obtained in step 1), and subjecting the mixture to ultrasonic reaction at a certain temperature for a period of time to obtain a black solution; The black solution was separated into solid and liquid, washed and dried, and the obtained solid product was Bi x Sb 1-x Nanoparticles; 3) Change Bi x Sb 1-x Nanoparticles, m-phenylenediamine, hexamethylenetetramine and poloxamer are blended and ground under a protective atmosphere to obtain a black viscous substance; The black viscous material was transferred to an autoclave for solidification, and the solidified material was annealed in flowing argon to obtain N-doped carbon-coated Bi x Sb 1-x Nanoparticle electrode materials.

2. The N-doped carbon-coated Bi according to claim 1 x Sb 1-x Nanoparticle electrode material, characterized in that The value range of X is based on the stoichiometric ratio, 0<X<1; Bi x Sb 1-x The mass proportion of nanoparticles in the core-shell structure is in the range of 55%-65%.

3. The N-doped carbon-coated Bi according to claim 1 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that The following steps are included: 1) Dispersing BiCl3 and SbCl3 together in water to obtain a milky white suspension; 2) slowly adding disodium ethylenediaminetetraacetate solution, polyvinylpyrrolidone solution and NaBH4 solution to the milky white suspension obtained in step 1), and subjecting the mixture to ultrasonic reaction at a certain temperature for a period of time to obtain a black solution; The black solution was separated into solid and liquid, washed and dried, and the obtained solid product was Bi x Sb 1-x Nanoparticles; 3) Change Bi x Sb 1-x Nanoparticles, m-phenylenediamine, hexamethylenetetramine and poloxamer are blended and ground under a protective atmosphere to obtain a black viscous substance; The black viscous material was transferred to an autoclave for solidification, and the solidified material was annealed in flowing argon to obtain N-doped carbon-coated Bi x Sb 1-x Nanoparticle electrode materials.

4. The N-doped carbon-coated Bi according to claim 3 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that The total concentration of BiCl3 and SbCl3 in the milky white suspension of step 1) is 0.03-0.1 mol / L; the molar ratio of BiCl3 to SbCl3 is X:(1-X), 0<X<1.

5. The N-doped carbon-coated Bi according to claim 3 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that Bi The molar ratio of Cl3+SbCl3, NaBH4, disodium ethylenediaminetetraacetate and polyvinylpyrrolidone is 1:(5-15):(1-2):(1-2).

6. The N-doped carbon-coated Bi according to claim 3 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that Na The concentration of BH4 solution is 5-7 mol / L, the concentration of disodium ethylenediaminetetraacetate solution is 2-3 mol / L, and the concentration of polyvinylpyrrolidone solution is 2-3 mol / L; NaBH4 solution, disodium ethylenediaminetetraacetate solution and polyvinylpyrrolidone solution all use water as solvent.

7. The N-doped carbon-coated Bi according to claim 3 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that In step 2), the ultrasonic time is 0.5-3h, and the ultrasonic temperature is 30-60°C.

8. The N-doped carbon-coated Bi according to claim 3 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that The Bi x Sb 1-x The mass ratio of nanoparticles, m-phenylenediamine, hexamethylenetetramine and poloxamer is (2-10):(2-4):1:(8-10).

9. The N-doped carbon-coated Bi according to claim 3 x Sb 1-x The method for preparing nanoparticle electrode material is characterized in that The curing temperature of step 3) is 100-200°C, and the curing time is 12-36h; the annealing temperature is 600-800°C, and the annealing time is 3-8h; the argon gas flow rate is 30-50mL / min.

10. The N-doped carbon-coated Bi according to claim 1 x Sb 1-x Application of nanoparticle electrode materials as negative electrode active materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Nitrogen-doped carbon-clad manganese oxide lithium ion battery composite cathode material, and preparation method and application of composite cathode material

    CN107369825A